Gender Inequality and Women’s Representation in Democratic Governance in Adamawa State - Wazakari , Rogers Roland; Yakubu, Yoila (Kashere Journal of Politics and International Relations, 2024)
This paper examines gender inequality and women’s representation in democratic governance in Adamawa State. The underrepresentation of women in political leadership in Adamawa State is a significant concern, reflecting broader societal issues of gender inequality. The patriarchal structure prevalent in Nigerian society, including Adamawa, continues to limit women's access to political power and decision-making processes. From 2019 to 2023, the political landscape in Adamawa has shown minimal improvement in women's representation. The objectives of the study are to identify the factors that combined to enforce discrimination against women in the 2019 and 2023 general election in Mubi-North, Yola-North and Numan Local Governments and to assess the impacts of gender disparity on democratic governance and societal progress in Adamawa State. The study adopts Marxist feminism as the theoretical framework. The used purposive sampling techniques while 150 questionnaires were distributed purposively for the study in the three senatorial zone in the state. The study used descriptive research design and chi-square was adopted as the method of data analysis. the study discovered lack of temporary quota system and inclusive, gender sensitive leadership promotes gender inequality, wrong societal mindset towards women participation in democratic governance and religious ideology limiting the roles of women in political participation. The study recommends adoption of quota system for women participation by political parties and waiver of payment of nomination fees by women in the state should be encouraged and all cultural and customary practices which discriminate, subordinate, oppress and hinder women participation in governance in Adamawa state should be abolished.